Avatar : the way of water [videorecording (Blu-Ray)] - Cameron, James, 1954-; Jaffa, Rick; Silver, Amanda; Friedman, Josh; Salerno, Shane; Worthington, Sam, 1976-; Saldana, Zoë, 1978-; Weaver, Sigourney, 1949-; Lang, Stephen, 1952-; Curtis, Cliff, 1968-; Moore, Joel David, 1977-; Pounder, C. C. H.; et al. (20th Century Studios, 2023)
Set more than a decade after the events of the first film, it begins to tell the story of the Sully family (Jake, Neytiri, and their kids), the trouble that follows them, the lengths they go to keep each other safe, the battles they fight to stay alive, and the tragedies they endure.